Lessons learnt from the first large-scale biodegradable FAD research experiment to mitigate drifting FADs impacts on the ecosystem. (February 2023) - Murua, Hilario; Zudaire, Iker; Tolotti, Mariana; Murua, Jefferson; Capello, Manuela; Basurko, Oihane C.; Krug, Iñigo; Grande, Maitane; Arregui, Igor; Uranga, Jon; Ferarios, Jose Maria; Sabarros, Philippe; et al.
Abstract: Drifting Fish Aggregating Devices (dFADs) are currently made with synthetic and non-biodegradable materials contributing to the increase of marine litter and other potential ecosystem impacts. Tuna RFMOs have promoted the research and progressive replacement of existing FADs by non-entangling biodegradable FADs (bioFADs). Here, we present the results of the first large-scale biodegradable FAD project in the Indian Ocean to develop and implement the use of non-entangling biodegradable dFADs. The bioFAD tested were fully non-entangling without netting minimizing completely the risk of entanglement. Tested bioFADs significantly contribute to the reduction of the synthetic plastic-based materials, increase the use of biodegradable materials and reduce the total material weight used in FADs, reducing their overall ecosystem impacts. The results of testing 771 bioFADs in real fishing conditions, showed that the fishing performance regarding presence/absence of tuna around dFADs, first day of tuna detection, proportion of FADs occupied by tuna, biomass aggregation underneath the FADs and catch per set between bioFADs and conventional dFADs were similar. This provides support for the efficacy of bioFADs regardless of the degradation experienced by the biodegradable materials tested. Although some bioFADs lasted up to one year, the degradation of the biodegradable material was important and some bioFADs lost their original structure after the study period, suggesting the need to find alternative designs for bioFADs that will suffer less structural stress than those bioFADs made of biodegradable material but with conventional design. The lessons learnt in this large-scale trial will contribute to refining the future designs of biodegradable FADs. Highlights: First large-scale biodegradable FAD project for tropical tuna fisheries in the Indian Ocean. Tested biodegradable FADs were fully non-entangling dFADs without netting, which minimized completely the risk of entanglement. Tested biodegradable FADs significantly contribute to the reduction of synthetic plastic-based materials. Tested biodegradable FADs increase the use of biodegradable materials. Tested biodegradable FADs reduce the total material weight used, reducing the overall ecosystem effects of FADs.